Correlations of hepatorenal functions among Diabetes patients attending tertiary care centers at Janakpurdham - Prakash, Satyam; Sah, Manohar Kumar; Sah, Vijay Kumar; Yadav, Om Prakash; Nayak, Ramesh; Yadav, Buddharam (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Diabetes mellitus (DM) has multiple long-term consequences linked to hepatorenal pathophysiology. The long-term DM is associated with evidences of abnormal liver and renal function. However, this yet to be clearly established, especially in rural low to mid-income countries like Nepal. Thus, we aimed to assess correlations of hepatorenal functions among diabetes patients attending tertiary care centers at Janakpurdham, Nepal. MATERIALS AND METHODS: A total of 227 diabetes patients attending medicine OPD of Janaki Medical College teaching hospital, Ramdiaya and Ram Janaki Hospital, Janakpur were enrolled. Under aseptic conditions, blood samples were collected. Semi-automatic analyzers were used for all biochemical investigations. Pearson correlation test was used to observe correlation between the various hepatorenal functions in diabetic patients. A p-value less than 0.005 was considered to be significant. RESULTS: Out of total 227 diabetes patients, 132 (58.1%) were male and 95 (41.9%) were female. Significant results were obtained regarding the correlation between the hepatic and renal profile with SGOT [SGPT (p=0.000); Urea (p=0.049)]. Significant correlations were found between the liver and renal profile with SGPT [Albumin (p=0.050); Creatinine (p=0.020)] and with urea [Creatinine (p=0.000)]. Similarly, there was a significant correlation between the renal profile and liver with urea [Creatinine (p=0.000)] and for creatinine [Sodium (p=0.000)]. CONCLUSIONS: Among diabetic patients, there was a substantial correlation between the liver and renal profiles. The etiology of various forms of diabetes mellitus is significantly influenced by hepatorenal factors among diabetics.